2012
DOI: 10.1371/journal.pone.0042017
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Provides Neuroprotection against Retinal Ganglion Cell Degeneration

Abstract: Retinal ganglion cell (RGC) degeneration occurs in numerous retinal diseases leading to blindness, either as a primary process like in glaucoma, or secondary to photoreceptor loss. However, no commercial drug is yet directly targeting RGCs for their neuroprotection. In the 70s, taurine, a small sulfonic acid provided by nutrition, was found to be essential for the survival of photoreceptors, but this dependence was not related to any retinal disease. More recently, taurine deprivation was incriminated in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 48 publications
2
58
0
1
Order By: Relevance
“…This suggests that taurine supplementation may be beneficial to prevent retinal degenerations that proceed with photoreceptor or RGC loss and in which light may also be a critical etiologic factor, such as inherited retinal degeneration, AMD, or glaucoma. 10,22,95,96 Finally, our data also suggest that taurine supplementation may be beneficial to prevent retinal degenerations in which S-cone degeneration is the initial event, such as the photoreceptor degenerations that are initiated or worsened by light.…”
Section: Rgc and Iprgc Degeneration: Contributions From Light And/or mentioning
confidence: 55%
“…This suggests that taurine supplementation may be beneficial to prevent retinal degenerations that proceed with photoreceptor or RGC loss and in which light may also be a critical etiologic factor, such as inherited retinal degeneration, AMD, or glaucoma. 10,22,95,96 Finally, our data also suggest that taurine supplementation may be beneficial to prevent retinal degenerations in which S-cone degeneration is the initial event, such as the photoreceptor degenerations that are initiated or worsened by light.…”
Section: Rgc and Iprgc Degeneration: Contributions From Light And/or mentioning
confidence: 55%
“…[47][48][49] A direct insult to RGCs under conditions of taurine depletion is also supported by a histopathological study of the retina from a vigabatrin-treated patient suggesting that RGCs were the primary site of the lesion. 11 Indeed, we have shown that pure RGCs survive better in culture with the addition of taurine in the medium, 49 consistent with the notion that in vivo taurine depletion can directly induce RGC degeneration. This RGC loss is consistent with the RGC degeneration observed in vigabatrin-treated animals also exhibiting taurine depletion.…”
Section: Taurine Depletion Causes Rgc Loss In the Mouse Retinamentioning
confidence: 96%
“…Interestingly, in 2012, Froger and colleagues reported a protective effect of the amino acid taurine against excitotoxicity showing increase RGC survival in vivo and in vitro and suggesting that enriched taurine nutrition can directly promote RGC survival (Froger et al, 2012). Moreover, nafamostat mesilate, a serine protease inhibitor showed protection against NMDA-induced neuronal and vascular damage in rat retinas (Tsuda et al, 2012).…”
Section: Neuroprotectantsmentioning
confidence: 99%